Pengaruh Customer Experience, Review Product dan Perceived Value terhadap Repurchase Intention Konsumen Shopee pada Mahasiswa Universitas Battuta - Sahgira, Nadia Nur; Dewi, Henny Purnama; Harahap, Zainy Cholis Muda (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
The rapid advancement of technology has significantly impacted various aspects of life, including the field of marketing. One of the effects is the increasing use of the internet and the growth of e-commerce in Indonesia, where Shopee has become the most widely used e-commerce platform. This study aims to analyze the influence of Customer Experience, Product Review, and Perceived Value on the Repurchase Intention of Shopee consumers among students of Battuta University. This study employs a quantitative approach with an associative research method. The population consists of 129 students from the 2023 cohort of the Faculty of Economics and Business at Battuta University. Using simple random sampling, 52 respondents were selected. Data were collected via WhatsApp questionnaires and analyzed using multiple linear regression in SPSS 25. The findings reveal that customer experience, product reviews, and perceived value significantly affect consumers’ intention to repurchase, both individually and collectively. These variables play a critical role in driving consumer behavior within e-commerce platforms. The analysis suggests that a substantial portion of repurchase intention is determined by these factors, emphasizing their strategic importance in online retail. The implications of this research highlight the need for e-commerce businesses to enhance customer engagement, encourage positive product feedback, and consistently deliver value. Strengthening these aspects can foster customer loyalty, improve satisfaction, and ultimately support sustainable business growth in the digital marketplace.